ANALISIS RESPON MASYARAKAT TERHADAP KEBIJAKAN VAKSIN COVID-19 DI INDONESIA MELALUI MEDIA BERITA - Suranto; Tunjung Sulaksono; Muhammad Farhan HR (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This study aims to see how the community responds to the Covid-19 vaccine policy carried out by the government in fortifying themselves against the transmission of the Covid-19 virus in Indonesia. This study used the Q-DAS (Qualitative Data Analysis Software) approach. In addition, in this study, data sources were taken from 2 different National News Media, with a total of 31 consisting of 15 news from Detik.com and 16 from Kompas.com. Apart from the news media, this research data source was also taken through websites and journals related to the author's research. The provision of a vaccine policy carried out by the government is the most appropriate solution for the community to break and reduce the chain of transmission of Covid-19. However, some people refuse this policy. The news media has a vital role in seeing, for various reasons, people who are ready and refuse to be vaccinated after the government implemented the Covid-19 vaccine policy in Indonesia. The results showed that the higher the type of Indonesian people's age group responded ready to be vaccinated, and the lower the type of Indonesian people's age group, the fewer those who responded were ready to be vaccinated. Most refuse to be vaccinated because the public responds doubtfully to the safety of vaccines